1989
DOI: 10.1164/ajrccm/139.3.682
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Hyaluronan (Hyaluronic Acid) in the Lung in Adult Respiratory Distress Syndrome

Abstract: The concentrations of hyaluronan (HA) were measured in bronchoalveolar lavage (BAL) fluid and serum from 12 patients with adult respiratory distress syndrome (ARDS). The median BAL fluid HA concentration was 353 micrograms/L, about six times higher than that seen in control patients (p less than 0.001). The median serum HA value was 619 micrograms/L, which was a 30-fold increase compared with that in the control patients (p less than 0.001). Another connective tissue component, type III procollagen peptide, wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
122
1
6

Year Published

1991
1991
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 167 publications
(140 citation statements)
references
References 9 publications
11
122
1
6
Order By: Relevance
“…Our measurements of PIIINP agree with previous studies indicating elevated PIIINP levels in BAL of patients with diffuse lung diseases, such as IPF, adult respiratory distress syndrome (ARDS), sarcoidosis and farmer's lung [5][6][7][8][10][11][12][13][14][15].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our measurements of PIIINP agree with previous studies indicating elevated PIIINP levels in BAL of patients with diffuse lung diseases, such as IPF, adult respiratory distress syndrome (ARDS), sarcoidosis and farmer's lung [5][6][7][8][10][11][12][13][14][15].…”
Section: Discussionsupporting
confidence: 89%
“…Thus, biochemical measurements of the balance between collagen synthesis and degradation would be helpful in monitoring the progress of fibrotic lung disease. In recent years, an assay for the procollagen type-III Nterminal propeptide (PIIINP) [3,4] has been used to assess collagen turnover both in serum and bronchoalveolar lavage fluid (BALF) from patients with idiopathic pulmonary fibrosis [5,6], sarcoidosis [7,8], adult respiratory distress syndrome [9,10], and farmer's lung [11][12][13]. Most of these studies have investigated PIIINP levels either in serum or BALF: In a few studies both PIIINP levels were investigated [10,14,15].…”
mentioning
confidence: 99%
“…Experimental studies have also demonstrated a link between the alveolar and interstitial accumulation of HYA and the intraalveolar oedema and oedema of the fragile alveolar structure [25]. The hypothesis that interstitial water trapped by HYA may result in impaired lung function is further supported by the clinical observations of a close relationship between high amounts of HYA recovered by BAL and reduced gas diffusion of the lung in patients with acute farmer's lung [20] or adult respiratory distress syndrome [26].…”
Section: Pulmonary Conditionsmentioning
confidence: 95%
“…The adult respiratory distress syndrome (ARDS), one of many possible components of MODS, is still a disease incompletely understood where a causal therapy is lacking. In human ARDS increased concentrations of hyaluronan in bronchoalveolar lavage fluid (BAL) has been found [27], and in a porcine model of sepsis-induced lung injury resembling ARDS, accumulation of interstitial hyaluronan has been seen [19]. This is in analogy to the increased amounts of hyaluronan found both interstitially and in BAL fluid in other interstitial inflammatory pulmonary diseases such as sarcoidosis and allergic alveolitis [28,29,30].…”
Section: Hyaluronan and Oedema Developmentmentioning
confidence: 99%